Bizmart books and such (students’ strategic entrepreneurship) / Putra Faizurrahman Zahid ... [et al.] - Zahid, Putra Faizurrahman; Zulqernain, Nurul Syaqirah; Nik Hassan, Nik Suriati; Mohamed, Siti Sarah; Ismail, Zurina; Bustaman, Hasnun Anip (2022)
Bizmart Book and Such is an entity of business in UiTM Kelantan developed for retail laboratory and as an income generator for the university. It aims to become as a referred business training centre for university students. The novelty of this strategic entrepreneurship model, it has simulated retail lab run in real-time, on real business transactions. Any student may have utilized their knowledge learned in the classroom and practice real retail business with guidance from the lecturers who has expertise in retail, marketing, management, and finance. Plus, they earn wages too. Starting from inventory purchase planning, stocking, displaying inventories and selling, students also involved in decision making activities such as deciding to add product lines or product mixes, purchase budgeting, pricing strategy initiative, and many more.